A review of 733 published trials on Bio-Mos®, a mannan oligosaccharide, and Actigen®, a second generation mannose rich fraction, on farm and companion animals. (20th May 2015) - Spring, P.; Wenk, C.; Connolly, A.; Kiers, A.
Summary: Mannan-oligosaccharides (MOS), as zootechnical feed ingredients, are widely used in animal nutrition. MOS has been commercially available since the launch of Bio-Mos® in the early 1990's and has a substantial body of scientific papers and practical examples of its efficacy. Since 1999, the use of MOS in animal feed has become more prominent, mainly due to the European ban on prophylactic antibiotic growth promoters in animal feed. MOS, with its ability to bind and limit the colonisation of gut pathogens, has proven to be an effective solution for antibiotic-free diets, as well as providing support for immunity and digestion. MOS has been shown to improve gastrointestinal health, thus improving wellbeing, energy levels and performance. Most MOS products, particularly those that have been scientifically developed, derive from the cell wall of the yeast, Saccharomyces cerevisiae . In 2009, a mannose-rich fraction (MRF) product was commercially launched as a 'second generation' of these MOS-type products, with enhanced activities in immune modulation and intestinal health. The purpose of this paper is to review the existing data on the benefits of MOS for all species of animals, discuss its mechanisms of action in vivo and compare the benefits of using second generation MRF to original MOS.